2017
DOI: 10.4172/2155-6148.1000709
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Hemodynamic Response and Complications in Patients with Difficult Airway Using Two Techniques-Retrograde and Fibreoptic Intubation

Abstract: Objective: The Aim of this study was to identify the hemodynamic response and success rate to awake retrograde endotracheal intubation (REI) and fiberoptic bronchoscope (FOB) assisted endotracheal intubation in difficult airway situation and to validate whether the REI can attenuate the hemodynamic response to tracheal intubation compared with the FOB assisted intubation. Design: Randomized Prospective Study.Methods: 64 adults, ASA I-II scheduled for elective surgery requiring endotracheal intubation were rand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
0
0
0
Order By: Relevance
“…In a 2017 study, Pokhriyal et al compared the hemodynamic response and success rate of awake retrograde endotracheal intubation (REI) and fiberoptic bronchoscope (FOB) assisted endotracheal intubation in difficult airway situations. They found that the maximum increase in heart rate and mean arterial pressure (MAP) occurred at the end of intubation in the REI group compared to the FOB group, while the FOB group's intubation took less time and had a higher success rate than the REI group [14]. In their retrospective observational analysis, Kriege et al found that tracheal intubation performed while awake was linked to a decreased rate of serious adverse outcomes compared to tracheal intubation performed while anesthetized [15].…”
Section: Discussionmentioning
confidence: 99%
“…In a 2017 study, Pokhriyal et al compared the hemodynamic response and success rate of awake retrograde endotracheal intubation (REI) and fiberoptic bronchoscope (FOB) assisted endotracheal intubation in difficult airway situations. They found that the maximum increase in heart rate and mean arterial pressure (MAP) occurred at the end of intubation in the REI group compared to the FOB group, while the FOB group's intubation took less time and had a higher success rate than the REI group [14]. In their retrospective observational analysis, Kriege et al found that tracheal intubation performed while awake was linked to a decreased rate of serious adverse outcomes compared to tracheal intubation performed while anesthetized [15].…”
Section: Discussionmentioning
confidence: 99%